Unisono - Dorota Jarząbek-Wasyl (Pamiętnik Teatralny, 2021)
This article offers a review of the recently published edited volume The Routledge Companion to Theatre and Performance Historiography (2021). The reviewer briefly presents the origins of this publication, its structure and mosaic-like design, as well as its main topics and methodology, and then she discusses selected contributions (of particular interest to the Polish reader) in more detail. Like any large-scale undertaking of this kind, this volume also raises concerns and doubts, especially with regard to following the postulated polyphonic and refreshing approach to performance history, as well as the limitations of institutional critique, whose outlook has its "blind spot," too.